2003
DOI: 10.1258/00222150360600887
|View full text |Cite
|
Sign up to set email alerts
|

Invasive sino-orbital aspergillosis: surgical decisions and dilemmas

Abstract: Invasive aspergillosis, one of the common paranasal sinus fungal infections, often secondarily involves the orbit. We report six such cases with orbital extension, all occurring in apparently immunocompetent hosts, to specifically address the difficult diagnostic and therapeutic issues involved. Limited biopsy procedures were often inconclusive, necessitating wide surgical excision to establish the histopathological diagnosis. Conservative orbital debridement proved adequate for cases with disease limited to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 14 publications
1
65
0
Order By: Relevance
“…Diagnosis can be suspected by the clinical aspect during surgery but needs confirmation by histology and microbiological methods, the results of which are available after 3-4 days. Cultures can be falsely negative in 40-50% of the cases (in our case series 75%) [1,18] and histopathological confirmation can be difficult when only necrotic tissue is obtained in biopsies [17] , as observed in other cases not part of this study. However, histopathology is evident to confirm or exclude an invasive fungal process, as well as to differentiate from other pathologies with radiological bone erosions as seen, e.g., in an allergic fungal rhinosinusitis [19] .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Diagnosis can be suspected by the clinical aspect during surgery but needs confirmation by histology and microbiological methods, the results of which are available after 3-4 days. Cultures can be falsely negative in 40-50% of the cases (in our case series 75%) [1,18] and histopathological confirmation can be difficult when only necrotic tissue is obtained in biopsies [17] , as observed in other cases not part of this study. However, histopathology is evident to confirm or exclude an invasive fungal process, as well as to differentiate from other pathologies with radiological bone erosions as seen, e.g., in an allergic fungal rhinosinusitis [19] .…”
Section: Discussionmentioning
confidence: 62%
“…However, histopathology is evident to confirm or exclude an invasive fungal process, as well as to differentiate from other pathologies with radiological bone erosions as seen, e.g., in an allergic fungal rhinosinusitis [19] . But even in negative biopsies, the possibility of an invasive mycosis must be kept in mind in patients with an erosive and destructive mass involving the cavernous sinus or the orbital apex [1,17] with a rapid decision of an antifungal treatment due to its high mortality. Amphotericin B, not being available for oral application, is associated with a high rate of nephrotoxicity (as seen in patients 1 and 2) and infusion reactions.…”
Section: Discussionmentioning
confidence: 99%
“…32 The chronicity of the disease along with a lack of acute signs or symptoms often masks the deadly nature of the infection and can delay diagnosis for months to years. Infections in healthy patients typically occur in specific geographic areas with warm, tropical, or desert climates such as the Middle East, Indian sub-continent, Southern United States 32 and Sudan.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Care should be taken to biopsy a sufficient amount of tissue, because many authors have reported a high rate of negative or inconclusive results. 32 Often, if suspicion for fungal infection is high, repeat biopsies are necessary.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation